Spatiotemporal Evolution and Influencing Factors of Ecological Civilization Construction in China - Mei Gai; Xiuqi Wang; Changli Qi (Complexity)
The construction of an ecological civilization is a strategic idea proposed based on the conditions of different countries and the laws governing social development. It is a new way to promote harmonious coexistence between humans and nature. Therefore, exploring the evolution characteristics and influence of ecological civilization in China is helpful for the country’s future development. This study uses the pentagon model, panel threshold regression model, and spatial analysis tool to explore the law of space-time differentiation and analyze regional coordination and ecological civilization construction in 31 provinces, cities, and autonomous regions in China from 2000 to 2018. During the study period, the construction of ecological civilization in China generally fluctuated; the spatial differentiation pattern of the eastern region was more developed than that of the central region, which was more developed than that of the western region. The regional coordination degree decreased in the order of east >central >northeast >west, and the degree of coordination in provinces and cities gradually shifted and finally accumulated to be reflected in the economy and environment in 2018. The most important factor affecting the development of ecological civilization was determined to be scientific research, followed by air quality and government information disclosure.